Stable transformation and expression of GhEXPA8 fiber expansin gene to improve fiber length and micronaire value in cotton - Bajwa, Kamran S.; Shahid, Ahmad A.; Rao, Abdul Q.; Bashir, Aftab; Aftab, Asia; Husnain, Tayyab (Frontiers in Plant Science, 2015)
Cotton fibre is multigenic trait controlled by number of genes. Previous studies suggest that one of these genes may be responsible for switching cotton fibre growth on and off to influence the fibre quality produced from a cotton seed. In the present study, the Gossypium hirsutum GhEXPA8 fibre expansin gene cloned into a pGA482 plant expression vector with a 2X 35S promoter and a CaMV terminator was introduced into local cotton variety NIAB 846 by using an Agrobacterium-mediated gene transformation. The neomycin phosphotransferase (NPTII) gene was used as a selection marker for screening of putative transgenic cotton plants. Integration and expression of the fibre expansin gene in cotton plants was confirmed with molecular techniques including Southern blot analyses, real-time PCR and cellulose assays. The data collected from three years of field performance of the transgenic cotton plants expressing GhEXPA8 showed that significant improvement has been made in fibre lengths and micronaire values as compared to control Gossypium hirsutum variety NIAB 846 cotton plants. Field data of fibre and morphological characteristics were also analyzed through statistical techniques. The results of this study support improvement of cotton fibre through genetic modification.